2020
DOI: 10.3390/jcm9082448
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Signature in Adipose Tissue of Crohn’s Disease Patients

Abstract: Crohn’s disease (CD) is characterized by compromised immune tolerance to the intestinal commensal microbiota, intestinal barrier inflammation, and hyperplasia of creeping fat (CF) and mesenteric adipose tissue (AT), which seems to be directly related to disease activity. Gut microbiota dysbiosis might be a determining factor in CD etiology, manifesting as a low microbial diversity and a high abundance of potentially pathogenic bacteria. We tested the hypothesis that CF is a reservoir of bacteria through 16S-rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Notably, the clinical status of patients seemed to be related to the microbiome signature, as those with the inactive disease showed a reduction in the abundance of pathogenic bacteria. These findings demonstrated that microbiota dysbiosis associated with CD pathophysiology is reflected in VAT, which might contribute to disease by potential bacterial translocation across a disrupted intestinal barrier [ 64 ].…”
Section: Adipose Tissue As An Active Endocrine Organ Visceral Adipose Tissue and Ibdmentioning
confidence: 99%
“…Notably, the clinical status of patients seemed to be related to the microbiome signature, as those with the inactive disease showed a reduction in the abundance of pathogenic bacteria. These findings demonstrated that microbiota dysbiosis associated with CD pathophysiology is reflected in VAT, which might contribute to disease by potential bacterial translocation across a disrupted intestinal barrier [ 64 ].…”
Section: Adipose Tissue As An Active Endocrine Organ Visceral Adipose Tissue and Ibdmentioning
confidence: 99%
“…CD ASCs have elevated proliferative, invasive, and phagocytic capacities, which may contribute to the creeping fat development 191 . In CD, ASCs exhibit a unique DNA methylation and gene expression profile 192 and CD creeping and mesenteric fat shows a microbiome signature that is absent in subcutaneous fat 193 . Immune‐non‐immune cell interactions are critical to the function of creeping fat.…”
Section: Creeping Fat and Smooth Muscle Hyperplasia In Intestinal Fibrosismentioning
confidence: 99%
“…47 Another important target site for PBT from the gut is the mesenteric adipose tissue when the leaky gut occurs in CD. 48,49 BT to mesenteric adipocytes i) occurs at a rate similar to the translocation to MLN; 50 ii) could represent a bacterial reservoir 51 iii) stimulating visceral fat for CRP-production; 50 and iv) in terms of the microbiota profile dependent on the clinical status in CD patients. 51 In addition, Ha et al characterized the subset of mucosal-associated gut bacteria that consistently translocated and remained viable in "creeping fat" defined as an expansion of mesenteric adipose tissue around the inflamed and fibrotic intestine in CD ileal surgical resections.…”
Section: Studies Reporting Reduced Taxa In CDmentioning
confidence: 99%
“…48,49 BT to mesenteric adipocytes i) occurs at a rate similar to the translocation to MLN; 50 ii) could represent a bacterial reservoir 51 iii) stimulating visceral fat for CRP-production; 50 and iv) in terms of the microbiota profile dependent on the clinical status in CD patients. 51 In addition, Ha et al characterized the subset of mucosal-associated gut bacteria that consistently translocated and remained viable in "creeping fat" defined as an expansion of mesenteric adipose tissue around the inflamed and fibrotic intestine in CD ileal surgical resections. 52 Translocation of C. innocuum was identified as a signature of this consortium i) with strain variation between mucosal and adipose isolates and ii) stimulating tissue remodeling via M2 macrophages leading to an adipose tissue barrier that serves to prevent systemic spread of translocated bacteria.…”
Section: Studies Reporting Reduced Taxa In CDmentioning
confidence: 99%
See 1 more Smart Citation